Immersive gaze sharing for enhancing education: An exploration of user experience and future directions - Yuval Kahlon; Weiheng Hu; Momoko Nakatani; Santosh Maurya; Takuya Oki; Jiang Zhu; Haruyuki Fujii (Computers & Education: X Reality)
Gaze sharing (GS) technology enhances communication between human interlocutors. Essentially, GS consists of sharing information regarding one's visual attention with another person, by automatically marking one's current point of interest on a digital display. The benefits of this technology for education have been demonstrated by researchers. However, since most GS systems relay gaze information using flat monitors, they impede natural communication between interlocutors who are co-located (as glancing at the display diverts their attention from the physical space). Acknowledging this limitation, immersive gaze sharing (IGS) systems have been recently developed. IGS systems utilize the power of Extended Reality (XR) technology to superimpose gaze information directly onto one's visual environment, and are therefore a promising tool for enhancing human communication in education. Currently, we know little regarding how users experience IGS, to guide its development. To bridge this gap, we have executed an exploratory user study of IGS with learners and instructors, using Mixed Reality (MR) technology. A quantitative and qualitative analysis of users' feedback and behavior has shed light on the differences between instructors and learners in terms of their needs, abilities and preferences. On this basis, guidelines for developing IGS systems are proposed, towards their integration into our future educational practices.